Incidencia de la preparación de fuerza en el rendimiento de los voleibolistas de Federación Deportiva Provincial de Loja, categoría juvenil, periodo 2023. - Quezada Carchi, Josué Sebastián (2024)
The Curricular Integration Project was conducted to investigate how the training of strength impacts the performance of volleyball players in the Loja Provincial Sports Federation. The study used a mixed quantitative-qualitative method with a correlational type and quasi-experimental design. An observation guide was established, and a survey, a physical pre-test, and a post-test of maximum strength, explosive strength, and resistance strength were applied to the sample of 16 athletes and one coach. The results were the following: in the observation guide, it was possible to know that there is an orderly sequence of training and physical preparation that significantly improves strength; in the survey, it was possible to identify that psychological, nutritional, and sports factors have a considerable impact on the performance of athletes. In the pre-test, maximum strength: high bar squat, 31,25% lifted between 81-90 kg, explosive power: Sargent jump, 56,25% reached between 286-295 cm and strength resistance: elbow flexion-extension on 31,25% it performs between 31-35 reps. With these results, a training plan for physical strength training was implemented to improve the performance of athletes. Once the proposal has been implemented, the results of the post-test maximum strength: high bar squat, 37,50% lift between 81-90 kg, explosive power: Sargent jump, 62,25% reach between 286-295 cm, and strength resistance: elbow flexion-extension 50% perform between 36-40 rep. After conducting a pre-test, it was found that some athletes had desirable percentages and ranges. However, with the implementation of a physical strength preparation plan, most athletes experienced an increase in both, indicating a significant improvement in volleyball players’ performance. Keywords: Physical preparation, strength, sports performance, training, volleyball.